Fasting Influence on Diabetic Emergency Visits in a Tertiary Care Hospital Throughout Ramadan and other Lunar Months - Zuneera Akram, Maryam Inayat, Sobia Akhtar, Rehana Perveen, Rehana Saeed, Juweria Abid, Muhammad Furqan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The ninth month of the Islamic calendar is Ramadan, during which Muslims fast from dawn till sunset. This extended fasting period may affect the management of diabetes in diabetic people. This study aimed to compare the number of visitors to the diabetic Emergency Room (ER) of a private tertiary care hospital in FB Area, Karachi, Pakistan, throughout Ramadan and other lunar months, with diabetes emergencies. Methodology: A retrospective cross-sectional study was conducted utilizing an electronic medical record review of patients with diabetes emergency who visited the ER of a tertiary care hospital between the ninth and eleventh lunar months during the previous two years. Patients with diabetes who visited the ER and were more than 18 years old were included. It established the frequency of ER visits, sociodemographic parameters, and clinical features. The relationships between variables were evaluated using the SPSS Software. Results: During the selected study period, the ER reported a total of 32,134 admissions. There were just 0.61 % of diabetes emergency visits. According to the inclusion criteria, 123 participants were included in the study (64.2% men and 35.7% women). The majority (51.2%) took oral hypoglycemic agents, and more than half (60.97%) had type 2 diabetes. There was a substantial variation in the prevalence of diabetes emergency visits between Shaban, Ramadan, and Shawal, 0.55, 0.32, and 0.27 %, respectively. However, the peak incidence did not occur during Ramadan. Despite identifying specific associations, the study showed no significant differences between the frequency of ER visits during Ramadan and the prior and subsequent lunar months regarding demographic and clinical variables and diabetes profile. Practical Implication: The following investigation will help in designing a plan with suitable diet and antidiabetic agents that will help in balancing the blood sugar levels as well as the glycemic index. Conclusion: In contrast to earlier studies, a decreasing prevalence trend was observed from Shaban to Ramadan to Shawal. This demonstrated that fasting throughout Ramadan has no negative effect on the occurrence of diabetes emergencies compared to other months. During the three-month study period, type 2 diabetes and insulin-treated patients with hyperglycemia were the leading cause of diabetic emergency room visits, with no significant variations across the months. These findings underscore the necessity for primary care physicians to thoroughly evaluate type 2 and insulin-treated individuals and provide comprehensive health education and counseling. Keywords: Ramadan, Diabetes, Fasting, Emergency visit, Antidiabetic agents, Diabetic Ketoacidosis, Hypoglycemia.